2015
DOI: 10.33549/physiolres.933034
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Carboxymethylated Mercaptotriazinoindole Inhibitor of Aldose Reductase Interferes With the Polyol Pathway in Streptozotocin-Induced Diabetic Rats

Abstract: The aim of the present work was to study the effect of 3mercapto-5H-1,2,4-triazino [5,6-b]indole-5-acetic acid (CMTI), an efficient aldose reductase inhibitor, on sorbitol accumulation in selected organs of streptozotocin-induced diabetic rats in vivo. In addition, the effect of CMTI on aldose reductase back reaction and on sorbitol dehydrogenase was determined. The model of experimental diabetes in male Wistar rats induced by streptozotocin was used. Experimental diabetes was induced by triple intraperitoneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…No signs or symptoms of cemtirestat toxicity developed during the 120-day treatment period. These observations are in accordance with our previously reported findings that revealed no acute toxicological manifestation of cemtirestat administered intragastrically (50 mg/kg/day) to male Wistar rats for five consecutive days (Soltesova Prnova et al 2015a).…”
Section: Animal Studiessupporting
confidence: 93%
“…No signs or symptoms of cemtirestat toxicity developed during the 120-day treatment period. These observations are in accordance with our previously reported findings that revealed no acute toxicological manifestation of cemtirestat administered intragastrically (50 mg/kg/day) to male Wistar rats for five consecutive days (Soltesova Prnova et al 2015a).…”
Section: Animal Studiessupporting
confidence: 93%
“…Chemistry. A commercially available compound, 2-(3thioxo-2H- [1,2,4]triazino [5,6-b]indol-5(3H)-yl)acetic acid (4) [CAS: 309283-89-4], recently identified as an ALR2 inhibitor 1 and reported also under the designation of cemtirestat, 3,6 is to our knowledge devoid of any literature report on its chemical synthesis. 7 Therefore, we developed a procedure for its Values of total energies, calculated as described in the experimental section, related by subtraction to the most stable tautomer in a given environment.…”
Section: ■ Resultsmentioning
confidence: 99%
“…In our previous study, carboxymethylated thioxotriazinoindoles were identified as AR inhibitors with high efficacy and selectivity. 1 Among the novel compounds, 2-(3-thioxo-2H- [1,2,4]triazino [5,6-b]indol-5(3H)-yl)acetic acid (4) (cemtirestat, CMTI, Figures 1 and 3) was found the most promising inhibitor endowed also with antioxidant activity. 2,3 Considering excellent "lead-likeness" of cemtirestat (4), we proceeded with optimization of its thioxotriazinoindole scaffold by replacement of sulfur with oxygen, with the aim to improve the inhibitory efficacy and selectivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The enzyme aldo-keto reductase (AR) determines the overall rate of the polyol pathway, and it also has a low affinity (K m > 100 mM) for glucose while in nondiabetic subjects, wherein the glucose concentration is normal. During the metabolism of glucose by the polyol pathway, a very minute percentage of total glucose is used [67,69]. In a hyperglycemic state, AR activation is achieved by increased intracellular glucose.…”
Section: Increased Intracellular Formation Of Advanced Glycationmentioning
confidence: 99%